HIGH-INTENSITY ELECTROMAGNETIC STIMULATION CAN REDUCE SPASTICITY IN POST-STROKE PATIENTS (International Journal of Physiotherapy, 2018)
Background: Level of spasticity in post-stroke patients allows for the predictability of the patient’s level of recovery. The study aimed to assess the anti-spastic effect of high-intensity electromagnetic field stimulation in post-stroke condition.Methods: 30 post-stroke patients, randomized into two groups participated. The treatment group (TG) was delivered ten therapies to spastic muscles with high-intensity electromagnetic stimulation. The control group (CG) was delivered ten electrotherapy sessions in the spastic muscle area combined with kinesiotherapy. Modified Ashworth Scale (MAS) was used as a primary outcome measure to evaluate the level of spasticity. Secondary outcome measure, Barthel Index of Activities of Daily Living (ADL) was used to evaluate the patient’s quality of life. Results were obtained pre-treatment, post-treatment and after 1-month follow-up was completed.Results: During the 1-month follow-up, TG improved results up to 66% decreasing spasticity from 2.33±0.90 in the beginning to 0.87±0.64 points on the MAS. The CG, during the 1-month follow-up, improved up to 31% decreasing spasticity from 2.13±0.74 in the beginning to 1.47±0.74 points on the MAS. According to Barthel Index, 81% level of improvement was observed in TG during 1-month follow-up vs. 72% level of improvement observed for the CG in a 1-month follow-up.Conclusion: The evaluation showed greater spasticity reduction in TG - 66% vs. 31% in the CG after the 1-month follow-up visit. Results suggest that high-intensity electromagnetic stimulation is an effective extracorporeal physical modality for spasticity management in post-stroke patients.